The Prevention of Ulcers Decubitus with Mobilization and The Usage of Olive Oil on Stroke Patients - Siti Cahaya Meliza; Kiking Ritarwa; Nur Asnah Sitohang (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Abstract: Decubitus ulcers are one of the problems experienced by bed rest patients, such as stroke patients, caused by immobilization. Prevention of decubitus ulcers can be done with mobilization and topical application of olive oil. Olive oil contains saturated fatty acids, unsaturated fatty acids, vitamin E, and phenols which are healthy for the skin. This research aims to identify the effects of mobilization and application of olive oil on the prevention of decubitus ulcers in stroke patients. A control group pretest-posttest quasi-experimental design was used in the research. Convenience (non-probability) sampling was also carried out, resulting in 64 research samples. Mobilization intervention of right-left oblique positions and application of olive oil on the area prone to decubitus ulcers were then executed for seven days. Data analysis using the Wilcoxon signed-rank test showed the effects of mobilization and application of olive oil on the preventions of decubitus ulcers in stroke patients with a value of P= <0,05. Abstrak: Ulkus dekubitus merupakan salah satu masalah yang dialami pasien tirah baring seperti pasien stroke, dengan faktor penyebabnya adalah immobilisasi, tindakan pencegahan ulkus dekubitus dapat dilkukan dengan mobilisasi dan pemberian bahan oles seperti minyak zaitun, minyak zaitun kandungannya terdiri dari asam lemak jenuh, asam lemak tak jenuh, vitamin E dan fenolik yang baik untuk kesehatan kulit. Penelitian ini bertujuan untuk mengidentifikasi pengaruh mobilisasi dan penggunaan minyak zaitun terhadap pencegahan ulkus dekubitus pada pasien stroke. Penelitian menggunakan desain Quasi-experimental dengan pretest- posttest with countrol gruopdesign.Convenience (Non-probability) dilakukan untuk pengambilan sampel, jumlah sampel penelitian 64. Intervensi mobilisasi miring kanan dan kiri kemudian bagian yang akan terjadi ulkus dekubitus diolesi minyak zaitun,intervensi dilakukan selama tujuh hari. Analisa data wilcoson signed -rank test menunjukan adanya pengaruh mobilisasi dan penggunaan minyak zaitun terhadap pencegahan ulkus dekubitus pada pasien stroke dangan nilai P= <0,05. Mobilisasi miring kanan dan kiri penggunaan minyak zaitun dapat mencegah ulkus dekubitus.